1999
DOI: 10.1046/j.1469-8137.1999.00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the ectomycorrhizal fungal genus, Rhizopogon

Abstract: The morphology and anatomy of ectomycorrhizas of Rhizopogon arctostaphyli, R. ellenae, R. flavofibrillosus, R. occidentalis, R. rubescens, R. smithii, R. subcaerulescens and R. truncatus synthesized on Ponderosa pine (Pinus ponderosa) in glasshouse conditions using spore slurries, are described and compared. All species produced a well‐developed Hartig net, and a well‐developed fungal mantle. The mantles of R. arctostaphyli, R. smithii and R. subcaerulescens ectomycorrhizas were two‐layered with outer mantle h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 26 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…In the present study it was also observed that the hyphal mantle underwent considerable variations as the colonization progressed like an initially thin and segregated mantle was replaced by a regular uniform mantle with two distinct layers of the different hyphal constitution: thinner and compacted hyphae in inner mantle relative to loosely aggregated hyphae in the outer mantle. Present observations are in analogy with the findings of a previous study that described two-layered subcaerulescens ectomycorrhizas synthesized on Pinus ponderosa in a glasshouse condition (Massicotte et al, 1999). Similarly, a two-layered mantle with loosely interwoven hyphae in outer mantle and compacted hyphae in inner mantle was seen in ectomycorrhiza of R. rubescens-Pinus sylvestris (Pachlewski and Pachlewska, 1974).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study it was also observed that the hyphal mantle underwent considerable variations as the colonization progressed like an initially thin and segregated mantle was replaced by a regular uniform mantle with two distinct layers of the different hyphal constitution: thinner and compacted hyphae in inner mantle relative to loosely aggregated hyphae in the outer mantle. Present observations are in analogy with the findings of a previous study that described two-layered subcaerulescens ectomycorrhizas synthesized on Pinus ponderosa in a glasshouse condition (Massicotte et al, 1999). Similarly, a two-layered mantle with loosely interwoven hyphae in outer mantle and compacted hyphae in inner mantle was seen in ectomycorrhiza of R. rubescens-Pinus sylvestris (Pachlewski and Pachlewska, 1974).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, root morphology in ectomycorrhiza of R. himalayensis and C. deodara roots was found to be analogous to the observations of Singh (1992), who noticed racemose to coralloid branching in this association. Similar branching was illustrated in various mycorrhizal associations of Rhizopogon species, for instance, coralloid in R. vulgaris-Pinus contorta Agerer et al, 1996); monopodial to dichotomous in R. subcaerulescens -Pseudotsuga menziesii (Massicotte et al, 1999); pinnate in R. vinicolor and R. parksii with P. menziesii (Massicotte, et al, 2000). Although, different root morphologies have also been reported in other Rhizopogon species, i.e.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Culture studies have noted distinct host-EcM specificities. Massicotte et al (1994) noted strong mycorrhization preferences among six tree species and 15 EcM fungal species, with none of the fungi having broad host ranges. However, a study of host-EcM fungal specificity among five tree species grown in soil indicated that specificity is significantly less strict, but still present (Massicotte et al, 1999).…”
Section: Ecm Community Selectionmentioning
confidence: 99%